Penerapan Home Care Dengan Pijat Oksitosin Terhadap Pengeluaran ASI Pada Ibu Nifas Di Kabupaten Bulukumba - Sumarni Sumarni; Husnul Khatimah; Fitriana Ibrahim; Jusni Jusni (Journal of Educational Innovation and Public Health, 2023)
Giving breast milk to babies is very important to support the baby's growth and development, and breast milk contains the best nutrition for newborn babies and is the only healthy food that babies need in the first month of life. However, not all mothers can provide exclusive breast milk for their babies, this is due to the mother's inability to overcome breastfeeding problems in the early period due to several factors that influence breast milk production including socio-cultural changes, psychological factors, physical factors of the mother, increasing promotion of formula milk, staff factors. health, mother's diet, baby's birth weight, use of contraception. One method of care that can be given to mothers to support smooth breastfeeding is an Oxytocin massage during home care services. The research aims to determine the effect of oxytocin massage on breast milk production in postpartum mothers, Bulukumba Regency. The design used in this research was Case Control and the sample in this research was 10 respondents. And the measuring instrument in this research uses a measuring cup. The results showed that breast milk production before the oxytocin massage treatment was 0% smooth and after the oxytocin massage treatment the average increase in breast milk production was 0.4 with the amount of smooth breast milk being 100%. Meanwhile, in the control group there was no increase in breast milk production. The results of the statistical test using the dependent t-test showed that the value was p=0.003, meaning there was a significant difference before the oxytocin massage and after the oxytocin massage. Conclusion There is an effect of Oxytocin Massage on breast milk production in postpartum mothers in Bulukumba Regency.